Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Làm tính chia:

Làm tính chia:

a) \(\left( {6{x^3} - 7{x^2} - x + 2} \right):\left( {2x + 1} \right)\)            

b) \(\left( {{x^4} - {x^3} + {x^2} + 3x} \right):\left( {{x^2} - 2x + 3} \right)\) ;

c) \(\left( {{x^2} + {y^2} + 6x + 9} \right):\left( {x + y + 3} \right)\) .

Hướng dẫn làm bài:

 

 

c) \(\left( {{x^2} + {y^2} + 6x + 9} \right):\left( {x + y + 3} \right)\)

=\(\left( {{x^2} + 6x + 9 - {y^2}} \right)\left( {x + y + 3} \right)\)

=\(\left[ {\left( {{x^2} + 2x.3 + {3^2}} \right) - {y^2}} \right]:\left( {x + y + 3} \right)\)

=\(\left[ {{{\left( {x + 3} \right)}^2} - {y^2}} \right]:\left( {x + y + 3} \right)\)

=\(\left( {x + 3 - y} \right)\left( {x + 3 + y} \right):\left( {x + y + 3} \right)\)

= x + 3 - y

= x - y + 3